SME research: SMEs' internationalization and collaborative innovation as two central topics in the field - David B. Audretsch; Christina Guenther (Journal of Business Economics, 2023)
SMEs' internationalization and innovation activities represent fundamental economic activities that are conducive to SMEs' individual success, but likewise contribute to the economic well-being of their home region and country. Therefore, understanding how some SMEs are innovative and internationally active has attracted significant scholarly attention within and beyond the SME research community. This paper highlights selected key findings from prior literature with regard to the context factors that facilitate SMEs' internationalization and innovation. In the latter case, we focus on innovation within inter-organizational collaborations. We conclude with directions for future SME research above and beyond SMEs' internationalization and innovation.
Keywords: 650; SME; Internationalization; Innovation; Collaboration